Keuangan Berkelanjutan Dalam Aksi: Menelaah Hubungan Antara Rantai Pasok Berkelanjutan, Akses Keuangan, Dan Adopsi Teknologi Di Ukm Indonesia - Misrofingah Misrofingah; Syamsu Rijal; Supriandi Supriandi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
MSMEs, or small and medium-sized enterprises, account for a sizable share of Indonesia's economy and are essential to the creation of jobs and the country's economic expansion. This study looks into how technology adoption, financial accessibility, and sustainable supply chain practices affect MSME performance and sustainable financing in Indonesian MSMEs. With 200 MSMEs, a cross-sectional survey design was used in a quantitative manner. Data analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings show a strong positive correlation between technology adoption, sustainable finance, sustainable supply chain practices, and MSME performance. It has been discovered that adoption of technology, access to financing, and sustainable supply chain practices all have a favorable impact on MSME performance and sustainable finance. The study emphasizes how crucial it is to include technology, finance, and sustainability into MSME operations in order to improve performance and promote sustainable development.